Comparison of immune response in broiler chickens after experimental inoculation with isolates of avian metapneumovirus subtypes A and B - P. S. Yaroslavtseva; M. A. Volkova; Z. B. Nikonova; N. S. Mudrak; Ir. A. Chvala (Ветеринария сегодня)
After experimental inoculation of broiler chickens with subtype A avian metapneumovirus isolate, mild clinical signs were observed on days 6-14 after inoculation. The infected chickens demonstrated slight increase of T-helpers activity in blood, poor specific antibody response, development of specific secretory antibodies. Subtype B avian metapneumovirus isolate caused a somewhat more obvious specific clinical signs in chickens compared with subtype A on days 5-15 after inoculation, however, in both experiments, clinical signs completely disappeared in 14-15 days after infection. The increase of relative number of cytotoxic T lymphocytes in blood and in spleen, specific antibody response in 50-70% of chickens and activation of local immune response in 50% of chickens were observed in inoculated chickens.